Providing straw to allow exploratory behaviour in a pig experimental system does not modify putative indicators of positive welfare: peripheral oxytocin and serotonin. (22nd January 2018) - Marcet Rius, M.; Cozzi, A.; Bienboire-Frosini, C.; Teruel, E.; Chabaud, C.; Monneret, P.; Leclercq, J.; Lafont-Lecuelle, C.; Pageat, P.
Abstract : Numerous studies have shown that providing straw to pigs can reduce undesirable behaviours such as aggression, tail biting and stereotypy. The measurement of various neuromodulators can be helpful in assessing the development of positive behaviours and overall animal welfare. The oxytocin release is frequently linked to positive emotions and positive welfare. It has been suggested that oxytocin modulates the serotoninergic system. This study aims to investigate the potential effect of straw provision in pigs on peripheral levels of oxytocin and serotonin. In total, 18 mini-pigs were involved in an exploratory study conducted in two parallel groups, Enriched ( n =10) and Control ( n =8) groups. Pigs were divided by group and housed in pens of two individuals. Straw was provided continuously only in Enriched group and renewed each day for 2 weeks. Two blood samples were drawn from each animal 5 to 10 min before providing the straw, and 15 min after providing straw, during the 1 st week, to analyse peripheral changes in oxytocin and serotonin before and after straw provision, and determine the existence of a putative short-term effect. The same procedure was carried out for Control group, without straw provision. Long-term effects of straw provision were also examined using blood samples drawn at the same hour from each animal in the 2 nd and 3 rd weeks. During this time, animals had the permanent possibility to explore the straw in Enriched group but not in Control group. At the end of each week, one animal-keeper completed two visual analogue scales for each mini-pig regarding the difficulty/ease to work with and handle it and its trust in humans. Results showed peripheral oxytocin increases in both groups after 2 weeks ( P =0.02). Results did not demonstrate any effect of providing straw to allow exploratory behaviour on peripheral serotonin. Other results were not significant. This preliminary study explored the relationship between peripheral oxytocin and serotonin and the presence of straw that allow pigs to perform exploratory behaviour, suggesting that there was no relationship between them. Some future studies may include crossing oxytocin and serotonin with other parameters, such as behavioural measures, to obtain more information about the true state of the animal and any possible relationship with pig welfare.